Hubungan Antara Sejarah Hukum dan Antropologi Hukum - Sutjipto Rahardjo (Antropologi Indonesia, 1989)
One of the characteristic of legal anthropology, according to the author, is the refusal law in its formal and absolute form. The Vollenhoven's thesis on the importance of studying law as it is rooted in the Indonesian society and culture can be regarded as the emergence of legal anthropology in Indonesia. Nevertheless, studies on law from anthropological viewpoint have just been intensified since 1970s. In describing the history of law and the position of legal anthropology in the legal history, the author reveals the main contribution of ideas from some law scientist. One among the ideas is the importance of analyzing the contents of law in recent context without precluding its historical dimension. The analysis on the history of law should constitute explanation on how events emerge and develop so as to provide better understanding on various rules, concept, and institutions of law at recent times. The legal anthropology provides us with such understanding on how certain laws emerge, develop, and change, since it analyzes law in its very "natural" context or as the manifestation of socio-cultural aspects of a society.